THE IMMERSION OF RESIN NANOHYBRID COMPOSITE IN LEMON (Citrus lemon) JUICE MAY DECREASE ITS HARDNESS PROPERTY : PERENDAMAN DENGAN PERASAN BUAH JERUK LEMON (Citrus Lemon) DAPAT MENURUNKAN KEKERASAN RESIN KOMPOSIT NANOHYBRID - IGN Bagus Tista; I Gusti Agung Ayu Hartini; Ida Ayu Gitasanthi karina Devi Ananta (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2020)
Composite resin is a restoration material that is often used because the composite resin has good aesthetic value like mimetic the teeth color. Composite resins have a physical and mechanical condition. One of the mechanical condition is hardness. The surface hardness of composite resins is the surface resistance of the composite resin material to the applied pressure. One of the factors influencing composite hardness is the food and beverages consumed. Consuming acidic drinks continuously for a long time period can erode composite resin filling. The purpose of this study was to determine the effect of soaking into a citrus lemon on the hardness of nanohybrid composite resin. This type of research was true experimental with pre-test post-test with control group design using 24 composite resin samples which are divided into 4 groups with 6 samples each. The groups in this study were nanohybrid composite resins soaked with citrus lemon and aqua dest for 60 minutes and 120 minutes. The hardness tested using a Vicker hardness tester. The results of the study using the LSD (Least Significant Difference) test showed that the significance value of p= 0.014 (p<0.05), which means that the use of citrus lemon for 120 minutes affected the hardness of nanohybrid composite resin. In conclusion, soaking with citrus lemon for 120 minutes reduces more the hardness of nanohybrid composite resin compared with soaking for 60 minutes.